Enamel matrix derivative has no effect on the chondrogenic differentiation of mesenchymal stem cells - Groeneveldt, Lisanne C.; Knuth, Callie; Witte-Bouma, Janneke; O'Brien, Fergal J.; Wolvius, Eppo B.; Farrell, Eric (Frontiers in Bioengineering and Biotechnology, 2014)
Background: Treatment of large bone defects due to trauma, tumour resection, or congenital abnormalities is challenging. Bone tissue engineering using mesenchymal stem cells (MSCs) represents a promising treatment option. However, the quantity and quality of engineered bone tissue are not sufficient to fill large bone defects. The aim of this study was to determine if the addition of enamel matrix derivative (EMD) improves in vitro chondrogenic priming of MSCs to ultimately improve in vivo MSC mediated endochondral bone formation. Methods: MSCs were chondrogenically differentiated in 200,0002.0x105 cell pellets in medium supplemented with TGFβ3 in the absence or presence of 1, 10, or 100 µg/mL EMD. Samples were analysed for gene expression of RUNX2, Col II, Col X, and Sox9. Protein, and glycoaminoglycan (GAG) production were also investigated via DMB assays, histology and immunohistochemistry. Osteogenic and adipogenic differentiation capacity were also assessed. Results: The addition of EMD did not negatively affect chondrogenic differentiation of adult human MSCs. EMD did not appear to alter GAG production or expression of chondrogenic genes. Osteogenic and adipogenic differentiation were also unaffected though a trend towards decreased adipogenic gene expression was observed. Conclusions: EMD does not affect chondrogenic differentiation of adult human MSCs. As such the use of EMD in combination with chondrogenically primed MSCs for periodontal bone tissue repair is unlikely to have negative effects on MSC differentiation.